Survival Benefit of Crossover Administration of Regorafenib and Trifluridine/Tipiracil Hydrochloride for Patients With Metastatic Colorectal Cancer: Exploratory Analysis of a Japanese Society for Cancer of the Colon and Rectum Multicenter Observational Study (REGOTAS) - Chida, Keigo; Kotani, Daisuke; Moriwaki, Toshikazu; Fukuoka, Shota; Masuishi, Toshiki; Takashima, Atsuo; Kumekawa, Yosuke; Kajiwara, Takeshi; Yamazaki, Kentaro; Komoda, Masato; Makiyama, Akitaka; Denda, Tadamichi; et al. (Frontiers in Oncology, 2021)
Background: The survival benefits of regorafenib (REG) and trifluridine/tipiracil hydrochloride (TFTD) have been demonstrated in chemorefractory patients with metastatic colorectal cancer (mCRC). However, the effects of crossover administration of REG and TFTD on patient survival remain unclear. The present study evaluated the association between exposure to REG and TFTD and overall survival (OS) in patients with mCRC using data from the REGOTAS study. Patients and Methods: We analyzed patients registered in the REGOTAS study, which retrospectively compared the efficacy and safety of the use of REG or TFTD as later-line chemotherapy for chemorefractory mCRC patients. We compared the survival outcomes of cohort A (treated using both REG and TFTD) and cohort B (treated using either REG or TFTD). Results: A total of 550 patients (cohort A, n = 252; cohort B, n = 298) met the inclusion criteria. The median OS was significantly increased in cohort A compared with cohort B [9.6 months (95% confidence interval (CI), 8.9–10.9 months) vs 5.2 months (95% CI, 4.4–6.0 months), P < 0.001]. Multivariate analysis revealed that cohort A was independently associated with a significant increase in OS (A vs B: Hazard ratios (HR), 0.58; 95% CI, 0.47–0.72; P < 0.001). Subgroup analysis adjusted using the multivariate Cox model revealed a consistently better trend in most subgroups for cohort A compared with cohort B. Conclusions: Our study revealed prolonged survival in patients treated with REG and TFTD. Therefore, all active agents, including REG and TFTD, should be made available to mCRC patients.